RepeatsDB-lite: a web server for unit annotation of tandem repeat proteins. Issue Volume 46:Issue W1(2018) (9th May 2018) - Hirsh, Layla; Paladin, Lisanna; Piovesan, Damiano; Tosatto, Silvio C E
Abstract: RepeatsDB-lite (http://protein.bio.unipd.it/repeatsdb-lite ) is a web server for the prediction of repetitive structural elements and units in tandem repeat (TR) proteins. TRs are a widespread but poorly annotated class of non-globular proteins carrying heterogeneous functions. RepeatsDB-lite extends the prediction to all TR types and strongly improves the performance both in terms of computational time and accuracy over previous methods, with precision above 95% for solenoid structures. The algorithm exploits an improved TR unit library derived from the RepeatsDB database to perform an iterative structural search and assignment. The web interface provides tools for analyzing the evolutionary relationships between units and manually refine the prediction by changing unit positions and protein classification. An all-against-all structure-based sequence similarity matrix is calculated and visualized in real-time for every user edit. Reviewed predictions can be submitted to RepeatsDB for review and inclusion.